THE ROLE OF DIGITAL LEADERSHIP IN SHAPING AVIATION EDUCATION: TRENDS, CHALLENGES, AND FUTURE DIRECTIONS - Jonah Gonzalo (jfpublisher, 2026)
Digital transformation in aviation has increased the importance of digital leadership for aviation educational institutions. The use of new technologies, including artificial intelligence, immersive simulations, and data-driven learning systems, is getting common, but the leadership processes to integrate them sustainably are still behind. Aviation education is one such area, which is generally regulated under law and safety-critical in nature, that illustrates this gap. The present study provides a systematic review of research on digital leadership in aviation education focusing on trends, challenges, and future directions. Following the PRISMA guidelines, the researchers carried out a thematic synthesis of thirty-eight scholarly articles published between 2020 and 2025 to find out trends in leadership behavior, technology adoption, and organizational change. The research shows an increase in the use of immersive and intelligent technologies, further, the digital leaders are performing the function of strategic change agents, and still, the same structural and cultural problems exist. Besides, the research space is getting more fragmented and at the same time maturing. Overall, the determining factor of digital transformation in education aviation is the capability of leaders.